Investigation of Silver Nitrate on Cytotoxicity and Apoptosis in MCF7 Human Breast Carcinoma Cells - Kaplan, Ayse; Mehtap Kutlu, Hatice (Asian Pacific Journal of Cancer Biology, 2020)
Background: Metal compounds have been studied in vitro for many years and these compounds’s effects are shown on tumors. Anticancer potential of silver and silver metal compounds is investigated in these days. A study on the in vitro interactions of silver nitrate (AgNO3) with MCF7 human breast carcinoma cells was performed to detect cytotoxic effects which induce apoptotic pathways. Materials and Methods: The cytotoxicity of silver nitrate which administered on MCF7 cells was assessed by MTT assay. The apoptotic influences of silver nitrate (IC50: inhibition concentration) were determined using Annexin V-FITC/PI, JC-1, TUNEL paraffin embedded and confocal microscopy assays. Silver nitrate induced cytotoxicity and apoptosis in MCF7 cells. Results: In this work, we demonstrated that the inhibition of cell growth which is time and dose dependent in MCF7 cells for 24, 48 and 72 hours. The inhibition concentration of silver nitrate (IC50) was found as 10 µM in MCF7 cells for 72 hrs. The early/late apoptotic and necrotic changes which occured with silver nitrate (IC50: 10µM) administered, were analyzed in the MCF7 cells for 72 hrs. However, the reduced mitochondrial membrane activity (ΔΨmt) was observed by silver nitrate-treated (IC50: 10µM) in the MCF7 cells for 72 hrs. In addition to these ﬁndings, a variety of apoptotic structures were demonstrated on MCF7 cells for 72 hrs. Conclusions: The results suggest that silver nitrate could be attributed as chemotherapeutic agent for medical applications in breast cancer treatment.